Modernization of Food Packaging Materials with Nanotechnology-A Mini Review - Balasubramanian, Deepika; Girigoswami, Agnishwar; Girigoswami, Koyeli (Recent Advances in Food Nutrition & Agriculture, 2023)
Food toxins can be of natural origin, chemicals, or inadvertent additives that get incorporated during food packaging and processing. When food is contaminated with bacteria or viruses, or other contaminants, serious foodborne diseases arise, causing severe health issues. To overcome these issues, proper food processing and packaging needs to be addressed to protect humans and animals from foodborne diseases. There are many smart food packaging materials that have evolved recently. Researchers enabled the use of nanomaterials in food packaging and have improved the efficacy of food packaging. In this mini-review, the objectives are to summarize the different types of food contaminants, conventional food packaging materials, and recent developments in nanotechnology-based food packaging materials.
Keywords: smart food packaging materials